2006
DOI: 10.1111/j.1365-2265.2006.02680.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma 1,25‐dihydroxyvitamin D levels in primary hyperparathyroidism depend on sex, body mass index, plasma phosphate and renal function

Abstract: Patients with PHPT have elevated plasma 1,25(OH)(2)D levels but, to a large extent, individual values overlap controls. The increase in plasma 1,25(OH)(2)D depends on renal function, hypophosphataemia and the female sex and is attenuated by high BMI. High plasma 1,25(OH)(2)D is associated with higher plasma calcium levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 47 publications
(137 reference statements)
4
37
1
Order By: Relevance
“…In accordance with a previous study (29), we found no difference between groups in p-25OHD, although low vitamin D status may be associated with higher PTH levels in PHPT and a more severe clinical presentation (13,29,36).…”
Section: Discussionsupporting
confidence: 80%
“…In accordance with a previous study (29), we found no difference between groups in p-25OHD, although low vitamin D status may be associated with higher PTH levels in PHPT and a more severe clinical presentation (13,29,36).…”
Section: Discussionsupporting
confidence: 80%
“…In short, plasma 25-hydroxyvitamin D (25OHD) is characteristically reduced independently of season, sex, or age (6). The excess PTH and the hypophosphatemia increase the renal production of 1,25-dihydroxyvitamin D (1,25(OH) 2 D) (7). This effect appears to be mitigated by the hypercalcemia (9,10) and possibly by increased plasma levels of fibroblast growth factor-23 (FGF23) (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of vitamin D metabolism in PHPT has previously been described in detail (6)(7)(8). In short, plasma 25-hydroxyvitamin D (25OHD) is characteristically reduced independently of season, sex, or age (6).…”
Section: Introductionmentioning
confidence: 99%
“…1-␣ hydroxylase to produce 1,25 dihydroxy vitamin D 3 (1,31,36,45,46), stimulation of ammoniagenesis (15,47), and stimulation of gluconeogenesis (42,47). The study of the effects of PTH on proximal tubule function is complicated by the fact that PTH receptors are expressed on both apical [brush-border membranes (BBM)] and basolateral membranes (BLM) (32).…”
mentioning
confidence: 98%
“…Specifically, PTH causes inhibition of sodium-dependent phosphate (NaPi) uptake (3,4,39,48,53) and sodium-hydrogen exchange (NHE) at the apical membrane (2, 7, 30, 53), inhibition of Na ϩ -K ϩ -ATPase ion transport (Na-K) at the basolateral membrane (17, 34), stimulation of 1-␣ hydroxylase to produce 1,25 dihydroxy vitamin D 3 (1,31,36,45,46), stimulation of ammoniagenesis (15, 47), and stimulation of gluconeogenesis (42, 47). The study of the effects of PTH on proximal tubule function is complicated by the fact that PTH receptors are expressed on both apical [brush-border membranes (BBM)] and basolateral membranes (BLM) (32).…”
mentioning
confidence: 99%